Asymptomatic Pulmonary Cryptococcosis And Tuberculosis Co-infection in an immunocompetent Host: A case report - Giri, Rashmi; Khetaan, Khusboo; Aryal, Gopi; Karthik, Ashish; Shrestha, Ashish; Gurung, Naresh; Shrestha, Sanjeet K. (Nepalese Respiratory Journal, 2023)
Pulmonary Cryptococcosis is a rare fungal infection that mostly occurs in immunocompromised host. However, with advancement in diagnostic approach like tissue biopsy, cryptococcal infections are now increasingly being recognised.In immunocompetent host, cryptococcal infection is often asymptomatic and rarely becomes disseminated. Symptom development in immunocompetent host largely depends on burden and virulence of pathogen. Due to similarities in clinical, radiological and pathological findings in Cryptococcosis, Tuberculosis and other fungal infections like Blastomycocosis, it is important to have a tissue biospy to confirm the diagnosis. The aim of this case report is to highlight the investigation necessary to diagnose both fungal infection and Tuberculosis due to similar clinical, radiological features in both. We report a case of Gene Xpert positive Tuberculosis and histopathology proven Pulmonary Cryptococcos in same patient.